2018
DOI: 10.4103/1673-5374.230272
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture and neuroregeneration in ischemic stroke

Abstract: Acupuncture is potentially beneficial for post-stroke rehabilitation and is considered a promising preventive strategy for stroke. Electroacupuncture pretreatment or treatment after ischemic stroke by using appropriate electroacupuncture parameters generates neuroprotective and neuroregenerative effects that increase cerebral blood flow, regulate oxidative stress, attenuate glutamate excitotoxicity, maintain blood-brain barrier integrity, inhibit apoptosis, increase growth factor production, and induce cerebra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 99 publications
1
30
0
Order By: Relevance
“…This technique has been widely used to treat post-stroke symptoms, and the mechanism of its effect has been described in a number of studies. [ 11 , 12 ] EA can be used to treat PSD: several clinical trials have been conducted, but there is still insufficient evidence regarding the efficacy and safety of EA for this condition. The present review aims to assess the efficacy and safety of EA in the treatment of dysphagia after stroke, in order to provide reliable evidence regarding the use of EA to practitioners and patients with PSD.…”
Section: Discussionmentioning
confidence: 99%
“…This technique has been widely used to treat post-stroke symptoms, and the mechanism of its effect has been described in a number of studies. [ 11 , 12 ] EA can be used to treat PSD: several clinical trials have been conducted, but there is still insufficient evidence regarding the efficacy and safety of EA for this condition. The present review aims to assess the efficacy and safety of EA in the treatment of dysphagia after stroke, in order to provide reliable evidence regarding the use of EA to practitioners and patients with PSD.…”
Section: Discussionmentioning
confidence: 99%
“…Those studies demonstrated the therapeutic effect of acupuncture in stroke rehabilitation. [ 11 , 14 , 27 , 28 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 ] Previous studies have indicated that acupuncture therapy is effective in improving balance function. [ 8 , 11 , 13 , 28 , 29 ] In some cases, the effectiveness can occur immediately after acupuncture. It also can affects the sensory perceptions.…”
Section: Discussionmentioning
confidence: 99%
“…Another neuroprotective mechanism of EA involves the downregulation of astrocytic S100B, which in turn deactivates p38 MAPK and its downstream substrate NF-κB. These effects subsequently reduce oxidative/nitrative stress and inhibit the TNF-α/tumor necrosis factor receptor type 1-associated DEATH domain protein (TRADD)/ Fas-associated protein with death domain (FADD)/cleaved caspase-8/cleaved caspase-3 apoptotic pathway in the ischemic cortical penumbra after reperfusion [ 89 , 201 , 202 , 203 , 204 , 205 , 206 , 207 ]. Both 5- and 25-Hz EA at acupoints GV20 and GV16 effectively downregulated reactive astrocytosis to exert neuroprotective effects against cerebral infarction-induced neuronal apoptosis, probably by activating the p38 MAPK/CREB signaling pathway [ 203 ].…”
Section: Cerebral Ischemiamentioning
confidence: 99%
“…Heat shock proteins (Hsp) significantly contribute to cellular regenerative processes in injured tissues because Hsp is upregulated during stem cell differentiation; however, the depletion or inhibition of Hsp70/Hsc70 impairs this process [ 206 ]. Hsp27 and Hsp70 reportedly contribute to intracellular protein repair after acute CI [ 206 , 207 , 208 , 209 , 210 , 211 ]. The dual phosphorylation of p38 MAPK was increased through early ischemia in an in vitro study wherein Hsp27 served as a terminal substrate of the p38 MAPK cascade.…”
Section: Cerebral Ischemiamentioning
confidence: 99%